Generation and characterization of a humanized ACE2 rat model for the study of SARS-CoV-2 and COVID-19 - Olson, Rachel M.; Nabli, Henda; Gentry, Bettina A.; Davis, Daniel J.; Franklin, Craig L.; Shaw, Mary L.; Bryda, Elizabeth C. (Frontiers in Microbiology, 2025)
Our goal was to generate new rat strains for the study of human pathogenic viruses such as SARS-CoV-2 that use ACE2 for entry into host cells. An over-expression rat model was generated using random transgenesis to integrate copies of human ACE2 under the control of the ubiquitously expressed CAG promoter into the rat genome. After transgene copy number, mRNA, and protein expression were confirmed, rats were challenged with the SARS-CoV-2 isolate USA-WA1/2020. Wild type rats are not susceptible to high titer challenge, while rats hemizygous for the ACE2 transgene lost significant body weight and displayed overt clinical signs of infection. This rat model will advance the understanding of COVID-19 and SARS-CoV-2 pathogenesis as well as accelerate the development of vaccines and antiviral therapies and can serve as an animal model for studies of the physiological role of ACE2.